Abnormal strong burn-in degradation of highly efficient polymer solar cells caused by spinodal donor-acceptor demixing - Li, Ning; Perea, José Darío; Kassar, Thaer; Richter, Moses; Heumüller, Thomas; Matt, Gebhard; Hou, Yi; Güldal, Nusret Sena; Chen, Haiwei; Chen, Shi; Langner, Stefan; Berlinghof, Marvin; et al. (Nature Communications, 2017)
The performance of organic solar cells is determined by the delicate, meticulously optimized bulk-heterojunction microstructure, which consists of finely mixed and relatively separated donor/acceptor regions. Here we demonstrate an abnormal strong burn-in degradation in highly efficient polymer solar cells caused by spinodal demixing of the donor and acceptor phases, which dramatically reduces charge generation and can be attributed to the inherently low miscibility of both materials. Even though the microstructure can be kinetically tuned for achieving high-performance, the inherently low miscibility of donor and acceptor leads to spontaneous phase separation in the solid state, even at room temperature and in the dark. A theoretical calculation of the molecular parameters and construction of the spinodal phase diagrams highlight molecular incompatibilities between the donor and acceptor as a dominant mechanism for burn-in degradation, which is to date the major short-time loss reducing the performance and stability of organic solar cells.

Controlling additive behavior to reveal an alternative morphology formation mechanism in polymer: Fullerene bulk-heterojunctions - Güldal, Nusret Sena; Berlinghof, Marvin; Kassar, Thaer; Du, Xiaoyan; Jiao, Xuechen; Meyer, Markus; Ameri, Tayebeh; Osvet, Andres; Li, Ning; Destri, Giovanni Li; Fink, Rainer; Ade, Harald; et al. (Journal of Materials Chemistry A, 2016)
One of the most employed morphology optimization methods to design better performing organic photovoltaic devices is ink formulation engineering with additives. In this work, by employing a suboptimal host solvent mixture and 1,8-diiodooctane (DIO) as a very optimal solvent for both components in poly-thieno[3,2b]thiophene-diketopyrrolopyrrole-co-thiophene (DPP-TT-T)-based bulk-heterojunctions (BHJ), an alternative, previously unknown mechanism of additive behavior on BHJ microstructure formation is presented. In situ characterization methods involving grazing incidence X-ray diffraction, white-light reflectometry, laser light scattering and photoluminescence during film drying reveal that the microstructure formation under the influence of DIO is led towards thermodynamic equilibrium during host solvent drying, and the kinetics of morphology formation (i.e. polymer crystallization, fullerene aggregation...) are controlled dominantly by the additive during its evaporation. Ex situ X-ray-based characterization methods, such as scanning transmission X-ray microspectroscopy (STXM) and resonant soft X-ray scattering (R-SoXS), additionally reveal that the microstructure of dried films favors smaller domain sizes with purer domains, smaller fullerene aggregates, bimodal polymer crystallization relative to the substrate and more face-on molecular orientation relative to the donor/acceptor interface, which at the end lead to better performing devices with power conversion efficiencies ranging from 1.25% to 4.68%.
Keywords: Engineering controlled terms: Additives; Fullerenes; Heterojunctions; Interfaces (materials); Light scattering; Microstructure; Molecular orientation; Morphology; Polymers; Solvents; Thiophene; X ray diffraction; X ray scattering Bulk heterojunction (BHJ); Characterization methods; Donor/acceptor interface; Grazing incidence X-ray diffraction; In-situ characterization; Microstructure formation; Organic photovoltaic devices; Power conversion efficiencies Engineering main heading: Polymer films

Crystal-structure of active layers of small molecule organic photovoltaics before and after solvent vapor annealing - Berlinghof, Marvin; Langner, Stefan; Harreiß, Christina; Schmidt, Ella; Siris, Rita; Bertram, Florian; Shen, Chen; Will, Johannes; Schindler, Torben; Prihoda, Annemarie; Rechberger, Stefanie; Duesberg, Georg; et al. (Zeitschrift fur Kristallographie - Crystalline Materials, 2020)
It is demonstrated by a detailed structural analysis that the crystallinity and the efficiency of small molecule based organic photovoltaics can be tuned by solvent vapor annealing (SVA). Blends made of the small molecule donor 2,2′-[(3,3′″,3″″,4′-tetraoctyl[2,2′:5′,2″:5″,2′″:5′″,2″″-quinquethiophene]-5,5″″-diyl)bis[(Z)-methylidyne(3-ethyl-4-oxo-5,2-thiazolidinediylidene)]]bis-propanedinitrile (DRCN5T) and the acceptor [6,6]-phenyl C71 butyric acid methyl ester (PC 71 BM) were annealed using solvent vapors with either a high solubility for the donor (tetrahydrofuran), the acceptor (carbon disulfide) or both (chloroform). The samples were analyzed by grazing-incidence wide-angle X-ray scattering (GIWAXS), electron diffraction, X-ray pole figures, and time-of-flight secondary ion mass spectrometry (ToF-SIMS). A phase separation of DRCN5T and PC 71 BM is induced by SVA leading to a crystallization of DRCN5T and the formation of a DRCN5T enriched layer. The DRCN5T crystallites possess the two dimensional oblique crystal system with the lattice parameters a = 19.2 Å, c = 27.1 Å, and β = 111.1° for the chloroform case. No major differences in the crystal structure for the other solvent vapors were observed. However, the solvent choice strongly influences the size of the DRCN5T enriched layer. Missing periodicity in the [010]-direction leads to the extinction of all Bragg reflections with k ≠ 0. The annealed samples are randomly orientated with respect to the normal of the substrate (fiber texture

Flexible sample cell for real-time GISAXS, GIWAXS and XRR: design and construction - Berlinghof, Marvin; Bär, Christian; Haas, D.; Bertram, F.; Langner, Stefan; Osvet, Andres; Chumakov, A.; Will, Johannes; Schindler, Torben; Zech, Tobias; Brabec, Christoph; Unruh, Tobias (Journal of Synchrotron Radiation, 2018)
Since the properties of functional materials are highly dependent on their specific structure, and since the structural changes, for example during crystallization, induced by coating and annealing processes are significant, the study of structure and its formation is of interest for fundamental and applied science. However, structure analysis is often limited to ex situ determination of final states due to the lack of specialized sample cells that enable real-time investigations. The lack of such cells is mainly due to their fairly complex design and geometrical restrictions defined by the beamline setups. To overcome this obstacle, an advanced sample cell has been designed and constructed; it combines automated doctor blading, solvent vapor annealing and sample hydration with real-time grazing-incidence wide- and small-angle scattering (GIWAXS/GISAXS) and X-ray reflectivity (XRR). The sample cell has limited spatial requirements and is therefore widely usable at beamlines and laboratory-scale instruments. The cell is fully automatized and remains portable, including the necessary electronics. In addition, the cell can be used by interested scientists in cooperation with the Institute for Crystallography and Structural Physics and is expandable with regard to optical secondary probes. Exemplary research studies are presented, in the form of coating of P3HT:PC61PM thin films, solvent vapor annealing of DRCN5T:PC71BM thin films, and hydration of supported phospholipid multilayers, to demonstrate the capabilities of the in situ cell.
Keywords: in situ; GIWAXS; GISAXS; XRR; thin film

Improving spray coated organic photodetectors performance by using 1,8-diiodooctane as processing additive - Montenegro Benavides, Cindy; Rechberger, Stefanie; Spiecker, Erdmann; Berlinghof, Marvin; Unruh, Tobias; Biele, Markus; Schmidt, Oliver; Brabec, Christoph; Tedde, Sandro F. (Organic Electronics, 2018)
In this work, we present and support the positive influence of 1,8-diiodooctane (DIO) as processing additive for the fabrication of solution processed near infrared (NIR) organic photodiodes (OPDs) based on the spray-coated blend of [6,6]phenyl-C70-butyric acid methyl ester (PC70BM) and poly[(2,5-bis(2-hexyldecyl)-2,3,5,6-tetrahydro-3,6-diox-opyrrolo[3,4-c]pyrrole-1,4-diyl)-alt-([2,2’:5′,2″-terthiophene]-5,5″-diyl)] (PDPP3T). Transmission electron microscopy (TEM) analysis show that the use of DIO improves donor–acceptor interfaces in the bulk heterojunction (BHJ) layer. Besides the enhancement of electron/hole transport pathways that leads to higher efficiencies, it reduces significantly the roughness of spray coated layers. The External Quantum Efficiency (EQE) is increased up to 35% at 900 nm and the dark current is decreased one order of magnitude in comparison to the reference down to 20 nA/cm2 at -5 V. The OPD's detectivity is increased from 1.66×1011 Jones to 3.34×1012 Jones and the linearity response is improved. A comprehensive morphological and electro-optical characterization of the generated layers and devices is the main focus of this work.
Keywords: DIO additive; organic photodetectors; spray coating; BHJ morphology

In Situ and Ex Situ Energy-Filtered Transmission Electron Microscopy Studies on the Nanomorpholgy Evolution of Organic Bulk Heterojunction Solar Cells - Harreiß, Christina; Langner, Stefan; Berlinghof, Marvin; Rechberger, Stefanie; Will, Johannes; Unruh, Tobias; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

In situ characterization methods for evaluating microstructure formation and drying kinetics of solution-processed organic bulk-heterojunction films - Güldal, Nusret Sena; Kassar, Thaer; Berlinghof, Marvin; Unruh, Tobias; Brabec, Christoph (Journal of Materials Research, 2017)
Recently, in situ characterization methods have attracted increasing attention, especially in organic photovoltaics (OPV) field, since they provide greater insight into the mechanism of film formation, thus help to identify optimized processing conditions used to process the most efficient organic bulk-heterojunction thin films. In combination with various powerful X-ray-based characterization methods, several studies observed the morphological changes under the influence of different processing conditions. In this review, we summarize the fundamentals and implementation of X-ray-based and optical characterization methods, utilized in in situ mode and introduce the reader a better overview of the information acquired from a given technique in terms of microstructure formation in OPV. While we give a chronological development of in situ characterization methods in the field of OPV, we discuss the interplay between thermodynamics of solutions and drying kinetics of different types of organic blends. © 2017 Materials Research Society.
Keywords: Characterization; Drying; Heterojunctions; Microstructure; Thermodynamics; Thin films; Characterization methods; In-situ characterization; Microstructure formation; Optical characterization; Organic bulk heterojunctions; Organic photovoltaics; Photovoltaic; Thermodynamics of solutions; In situ processing

Interface between Water-Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir, 2020)
The mechanism behind the stability of organic nanoparticles prepared by liquid antisolvent (LAS) precipitation without a specific stabilizing agent is poorly understood. In this work, we propose that the organic solvent used in the LAS process rapidly forms a molecular stabilizing layer at the interface of the nanoparticles with the aqueous dispersion medium. To confirm this hypothesis, n-octadecyltrichlorosilane (OTS)-functionalized silicon wafers in contact with water-solvent mixtures were used as a flat model system mimicking the solid-liquid interface of the organic nanoparticles. We studied the equilibrium structure of the interface by X-ray reflectometry (XRR) for water-solvent mixtures (methanol, ethanol, 1-propanol, 2-propanol, acetone, and tetrahydrofuran). The formation of an organic solvent-rich layer at the solid-liquid interface was observed. The layer thickness increases with the organic solvent concentration and correlates with the polar and hydrogen bond fraction of Hansen solubility parameters. We developed a self-consistent adsorption model via complementing adsorption isotherms obtained from XRR data with molecular dynamics simulations.
CRIS-Team Scopus Importer:2020-10-30

Interface Molecular Engineering for Laminated Monolithic Perovskite/Silicon Tandem Solar Cells with 80.4% Fill Factor - Ramírez Quiroz, César Omar; Spyropoulos, Georgios; Salvador, Michael; Roch, Loïc M.; Berlinghof, Marvin; Darío Perea, José; Forberich, Karen; Dion-Bertrand, Laura Isabelle; Schrenker, Nadine J.; Classen, Andrej; Gasparini, Nicola; Chistiakova, Ganna; et al. (Advanced Functional Materials, 2019)
A multipurpose interconnection layer based on poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT:PSS), and d-sorbitol for monolithic perovskite/silicon tandem solar cells is introduced. The interconnection of independently processed silicon and perovskite subcells is a simple add-on lamination step, alleviating common fabrication complexities of tandem devices. It is demonstrated experimentally and theoretically that PEDOT:PSS is an ideal building block for manipulating the mechanical and electrical functionality of the charge recombination layer by controlling the microstructure on the nano- and mesoscale. It is elucidated that the optimal functionality of the recombination layer relies on a gradient in the d-sorbitol dopant distribution that modulates the orientation of PEDOT across the PEDOT:PSS film. Using this modified PEDOT:PSS composite, a monolithic two-terminal perovskite/silicon tandem solar cell with a steady-state efficiency of 21.0%, a fill factor of 80.4%, and negligible open circuit voltage losses compared to single-junction devices is shown. The versatility of this approach is further validated by presenting a laminated two-terminal monolithic perovskite/organic tandem solar cell with 11.7% power conversion efficiency. It is envisioned that this lamination concept can be applied for the pairing of multiple photovoltaic and other thin film technologies, creating a universal platform that facilitates mass production of tandem devices with high efficiency.
Keywords: density functional theory; lamination; molecular dynamics; monolithic tandem; perovskite/silicon; transparent-conductive-adhesive

Memory Effect of Self-Assembled PS-b-PEO Block Copolymer Films with Selectively Embedded Functionalized TiO2 Nanoparticles - Kirschner, Johannes; Will, Johannes; Rejek, Tobias; Portilla Berlanga, Luis; Berlinghof, Marvin; Schweizer, Peter; Spiecker, Erdmann; Steinrück, Hans-Georg; Unruh, Tobias; Halik, Marcus (Advanced Materials Interfaces, 2017)
The memory effect in organic thin film transistors is described with a dielectric hybrid material composed of selectively localized charge trapping titania nanoparticles in a polystyrene-b-polyethyleneoxide (PS-b-PEO) diblock copolymer film. Upon solvent annealing in toluene atmosphere, the films readily form nanophase-separated features of PEO cylinders in a matrix of PS. X-ray reflectivity (XRR) investigations reveal that the TiO2 particles are selectively distributed in the top half of the hybrid layers. Applied in organic thin film transistor devices with 2-tridecyl-[1]benzothieno[3,2-b][1]benzothiophen (mono-C13-BTBT) semiconductor, the hybrid layers induce clockwise drain current hysteresis with promising memory ratio, long-term stability, and endurance. The occurrence of nonvolatile charge trapping directly relates to the hierarchically assembled nanostructure of the nanoparticles in the block copolymer since reference devices with PS homopolymers blended with TiO2 are found to be hysteresis free. Morphological characterization of the hybrid dielectric layers by atomic force microscopy and XRR experiments is presented to shed light on the internal electron density distribution. The layers are subsequently tested in capacitor stacks and transistors.

Morphology-Controlled Organic Solar Cells Improved by a Nanohybrid System of Single Wall Carbon Nanotubes Sensitized by PbS Core/Perovskite Epitaxial Ligand Shell Quantum Dots - Soltani, Rezvan; Katbab, Ali Asghar; Sytnyk, Mykhailo; Amin, Atefeh Y.; Killilea, Niall Andrew; Berlinghof, Marvin; Ahmadloo, Farzaneh; Osvet, Andres; Unruh, Tobias; Heiß, Wolfgang; Ameri, Tayebeh (Solar RRL, 2017)
In the present work, a new solution processed nanohybrid system comprising of single-wall carbon nanotubes (SWCNTs) loaded by PbS quantum dots (QD) capped with an epitaxial ligand shell of methylammonium lead iodide perovskite clusters (MA4PbI6) is designed and fabricated. Attachment of PbS/PbI6 QDs on the surface of SWCNT is followed and evidenced by performing Fourier Transform Infrared Spectroscopy, X-ray photoelectron spectroscopy, and Field Emission Scanning Electron Microscopy. The steady state and dynamic photoluminescence results reveal efficient charge transfer from photo-excited PbS/PbI6 to SWCNTs. Very low amount (0.3 wt.%) of the as-synthesized PbS/PbI6-SWCNT is further incorporated into a polymeric solar cell containing P3HT and PC61BM and exhibits a power conversion efficiency improvement of around 15% compared to the P3HT:PC61BM bulk heterojunction reference solar cell. Significantly, loading perovskite capped PbS QDs on the surface of SWCNT works more efficient rather than incorporating PbS/PbI6 or SWCNT separately onto the composition of the photoactive layer. While PbS/PbI6 broaden the absorption window of photoactive layer and enhance the photon harvesting, their loading on the SWCNT has a significant influence on the faster exciton splitting by efficient electron transfer as well as keeping the desired crystallinity and nanoscale morphology of host matrix upon addition of QDs.

Oxidative stress-induced posttranslational modifications of alpha-synuclein: specific modification of alpha-synuclein by 4-hydroxy-2-nonenal increases dopaminergic toxicity - Xiang, Wei; Schlachetzki, Johannes; Helling, Stefan; Bussmann, Julia C.; Berlinghof, Marvin; Schäffer, Tilman; Marcus, Katrin; Winkler, Jürgen; Klucken, Jochen; Becker, Cord-Michael; Klucken, Jochen (Molecular and Cellular Neuroscience, 2013)
Aggregation and neurotoxicity of misfolded alpha-synuclein (?Syn) are crucial mechanisms for progressive dopaminergic neurodegeneration associated with Parkinson's disease (PD). Posttranslational modifications (PTMs) of ?Syn caused by oxidative stress, including modification by 4-hydroxy-2-nonenal (HNE-?Syn), nitration (n-?Syn), and oxidation (o-?Syn), have been implicated to promote oligomerization of ?Syn. However, it is yet unclear if these PTMs lead to different types of oligomeric intermediates. Moreover, little is known about which PTM-derived ?Syn species exerts toxicity to dopaminergic cells. In this study, we directly compared aggregation characteristics of HNE-?Syn, n-?Syn, and o-?Syn. Generally, all of them promoted ?Syn oligomerization. Particularly, HNE-?Syn and n-?Syn were more prone to forming oligomers than unmodified ?Syn. Moreover, these PTMs prevented the formation of amyloid-like fibrils, although HNE-?Syn and o-?Syn were able to generate protofibrillar structures. The cellular effects associated with distinct PTMs were studied by exposing modified ?Syn to dopaminergic Lund human mesencephalic (LUHMES) neurons. The cellular toxicity of HNE-?Syn was significantly higher than other PTM species. Furthermore, we tested the toxicity of HNE-?Syn in dopaminergic LUHMES cells and other cell types with low tyrosine hydroxylase (TH) expression, and additionally analyzed the loss of TH-immunoreactive cells in HNE-?Syn-treated LUHMES cells. We observed a selective toxicity of HNE-?Syn to neurons with higher TH expression. Further mechanistic studies showed that HNE-modification apparently increased the interaction of extracellular ?Syn with neurons. Moreover, exposure of differentiated LUHMES cells to HNE-?Syn triggered the production of intracellular reactive oxygen species, preceding neuronal cell death. Antioxidant treatment effectively protected cells from the damage triggered by HNE-?Syn. Our findings suggest a specific pathological effect of HNE-?Syn on dopaminergic neurons.
EVALuna2:4685

Real-time evaluation of thin film drying kinetics using an advanced, multi-probe optical setup - Güldal, Nusret Sena; Kassar, Thaer; Berlinghof, Marvin; Ameri, Tayebeh; Osvet, Andres; Pacios, Roberto; Li Destri, Giovanni; Unruh, Tobias; Brabec, Christoph (Journal of Materials Chemistry C, 2016)
Solution-processed organic photovoltaic devices are advantageous due to their low-cost large area manufacturing techniques, such as slot-die coating, gravure printing and roll-to-roll coating. The final microstructure of a polymer:fullerene bulk-heterojunction (BHJ) film is a fine interplay between solution thermodynamics (e.g. solubility, miscibility...) and kinetics (e.g. solvent evaporation, polymer ordering, phase separation...) during the drying process. In order to design better performing organic photovoltaic devices, gaining knowledge over the drying properties of polymer:fullerene thin films is essential. A novel in situ thin film drying characterization chamber, equipped with white-light reflectometry, laser light scattering and photoluminescence, is presented in combination with grazing-incidence X-ray diffraction on two different polymer:fullerene bulk heterojunctions based on poly-(3-hexylthiophene-2,5-diyl) (P3HT) and polythieno[3,2b]thiophene-diketopyrrolopyrrole-co-thiophene (DPP-TT-T) polymers. With photoluminescence applied for the first time as an in situ method for such drying studies, these single-chamber measurements track the fine interplay between thermodynamics and kinetics of thin film drying and provide invaluable information on solution behavior and microstructure formation.
Keywords: Engineering controlled terms: Coatings; Drying; Fullerenes; Heterojunctions; Kinetics; Light scattering; Microstructure; Phase separation; Photoluminescence; Plastic coatings; Polymer films; Polymers; Rolls (machine components); Solubility; Thermodynamics; Thiophene; X ray diffraction Bulk heterojunction (BHJ); Grazing incidence X-ray diffraction; Manufacturing techniques; Microstructure formation; Organic photovoltaic devices; Poly(3-hexylthiophene-2; 5-diyl); Solution thermodynamics; Thermodynamics and kinetics Engineering main heading: Thin films

Real-Time Investigation of Intercalation and Structure Evolution in Printed Polymer:Fullerene Bulk Heterojunction Thin Films - Kassar, Thaer; Güldal, Nusret Sena; Berlinghof, Marvin; Ameri, Tayebeh; Kratzer, Andreas; Schroeder, Bob C.; Li Destri, Giovanni; Hirsch, Andreas; Heeney, Martin; Mcculloch, Iain; Brabec, Christoph; Unruh, Tobias (Advanced Energy Materials, 2016)
The complex intermixing morphology is critical for the performance of the nanostructured polymer:fullerene bulk heterojunction (BHJ) solar cells. Here, time resolved in situ grazing incidence X-ray diffraction and grazing incidence small angle X-ray scattering are used to track the structure formation of BHJ thin films formed from the donor polymer poly(2,5-bis(3-hexadecylthiophen-2-yl)thieno[3,2-b]thiophene) with different fullerene derivative acceptors. The formation of stable bimolecular crystals through the intercalation of fullerene molecules between the side chains of polymer crystallites is investigated. Such systems exhibit more efficient exciton dissociation but lower photo-conductance and faster decay of charges. On the basis of the experimental observations, intercalation obviously takes place before or with the formation of the crystalline polymer domains. It results in more stable structures whose volume remains constant upon further drying. Three distinct periods of drying are observed and the formation of unidimensional fullerene channels along the π-stacking direction of polymer crystallites is confirmed.
Keywords: fullerenes; grazing incidence diffraction; intercalation dynamics; organic solar cells; thin films

Real-Time Study on Structure Formation and the Intercalation Process of Polymer: Fullerene Bulk Heterojunction Thin Films - Kassar, Thaer; Berlinghof, Marvin; Güldal, Nusret Sena; Schmutzler, Tilo; Zontone, Federico; Brandl, Marco; Metwalli, Ezzeldin; Will, Johannes; Li, Ning; Ameri, Tayebeh; Brabec, Christoph; Unruh, Tobias (Solar RRL, 2020)
Fullerene intercalation between the side chains of conjugated polymers has a detrimental impact on both charge separation and charge transport processes in bulk heterojunction (BHJ) organic photovoltaic cells (OPVs). In situ grazing incidence X-ray scattering experiments allow to characterize the structure formation, drying kinetics, and intercalation in blends of phenyl-c61-butyric acid methyl ester (PC60BM) and poly(2,5-bis(3-tetradecylthiophen-2-yl)thieno[3,2-b]thiophene) named (pBTTT-C14) from their 1,2-orthodichlorobenzene (oDCB) solutions with different volume fractions of dodecanoic acid methyl ester (Me12) as a solvent additive. The structure formation process during evaporation of the solvent:additive mixture can be described by five periods, which are correlated to a multistep contraction of the lamellar stacking of the bimolecular crystals. The onset of crystallization is delayed by increasing the additive volume fraction in the coating solution leading to a promoted crystallinity. A conclusive picture of fullerene intercalation and additive-tuned structural evolution during the drying of thin films of the polymer:fullerene BHJ blends will be presented.
CRIS-Team WoS Importer:2020-02-04

Robot-Based High-Throughput Engineering of Alcoholic Polymer: Fullerene Nanoparticle Inks for an Eco-Friendly Processing of Organic Solar Cells - Xie, Chen; Tang, Xiaofeng; Berlinghof, Marvin; Langner, Stefan; Chen, Shi; Späth, Andreas; Li, Ning; Fink, Rainer; Unruh, Tobias; Brabec, Christoph (ACS Applied Materials and Interfaces, 2018)
Development of high-quality organic nanoparticle inks is a significant scientific challenge for the industrial production of solution processed organic photovoltaics (OPVs) with eco-friendly processing methods. In this work, we demonstrate a novel, robot-based, high throughput procedure performing automatic poly(3-hexylthio-phene-2,5-diyl) and indene-C-60 bisadduct nanoparticle ink synthesis in nontoxic alcohols. A novel methodology to prepare particle dispersions for fully functional OPVs by manipulating the particle size and solvent system was studied in detail. The ethanol dispersion with a particle diameter of around 80-100 nm exhibits reduced degradation, yielding a power conversion efficiency of 4.52%, which is the highest performance reported so far for water/alcohol-processed OPV devices. By successfully deploying the high-throughput robot-based approach for an organic nanoparticle ink preparation, we believe that the findings demonstrated in this work will trigger more research interest and effort on eco-friendly industrial production of OPVs.
Keywords: organic photovoltaics; eco-friendly industrial production; robot-based systems; high-throughput organic nanoparticle synthesis; stable organic nanoparticle inks; organic nanoparticle size control

Understanding and Controlling the Evolution of Nanomorphology and Crystallinity of Organic Bulk-Heterojunction Blends with Solvent Vapor Annealing - Harreiß, Christina; Langner, Stefan; Wu, Mingjian; Berlinghof, Marvin; Rechberger, Stefanie; Will, Johannes; Conroy, Michele; Bangert, Ursel; Unruh, Tobias; Brabec, Christoph; Spiecker, Erdmann (Solar RRL, 2022)
Solvent vapor annealing (SVA) has been shown to significantly improve the device performance of organic bulk-heterojunction solar cells, yet the mechanisms linking nanomorphology, crystallinity of the active layer, and performance are still largely missing. Here, the mechanisms are tackled by correlating the evolution of nanomorphology, crystallinity, and performance with advanced transmission electron microscopy methods systematically. Model system of DRCN5T:PC71BM blends are SVA treated with four solvents differing in their donor and acceptor solubilities. The choice of solvent drastically influences the rate at which the maximum device efficiency establishes, though similar values can be achieved for all solvents. The donor solubility is identified as a key parameter that controls the kinetics of diffusion and crystallization of the blend molecules, resulting in an inverse relationship between optimal annealing time and donor solubility. For the highest efficiency, optimum domain size and single-crystalline nature of DRCN5T fibers are found to be crucial. Moreover, the π–π stacking orientation of the crystallites is directly revealed and related to the nanomorphology, providing insight into the charge carrier transport pathways. Finally, a qualitative model relating morphology, crystallinity, and device efficiency evolution during SVA is presented, which may be transferred to other light-harvesting blends.
Created from Fastlane, Scopus look-up
Keywords: crystallinity; EF-ED; EFTEM; nanomorphology; organic BHJ solar cells; small molecules; SVA